TINJAUAN HUKUM PENEGAKAN HAK RESTITUSI TERHADAP KORBAN TINDAK PIDANA PENGANIAYAAN: Studi Kasus Nomor 1127/Pid.B/2023/PN Medan - Aldo Bevindra (Universitas Harapan Medan, 2025)
This research aims to analyze the mechanism for enforcing the right to restitution for victims of assault crimes, the legal regulations governing such rights, and the legal considerations of the judge in Decision Number 1127/Pid.B/2023/PN Mdn. The study employs a normative juridical research method using statutory and case approaches, with data collected through library research involving primary, secondary, and tertiary legal materials.The results indicate that the mechanism for enforcing the right to restitution for victims of assault crimes has been comprehensively regulated under Supreme Court Regulation Number 1 of 2022 concerning the Procedures for Handling and Granting Restitution and Compensation to Crime Victims, and Law Number 31 of 2014 concerning the Protection of Witnesses and Victims. Restitution serves as a form of the offender’s responsibility to compensate for the material and immaterial losses suffered by the victim. In Decision Number 1127/Pid.B/2023/PN Mdn, the judge considered principles of restorative justice and proportionality in determining the amount of restitution to be paid by the defendant.The study concludes that the legal framework on restitution provides a sufficient basis for victim protection, yet its implementation still faces challenges, including limited understanding among law enforcement officers and the suboptimal role of the Witness and Victim Protection Agency (LPSK). Therefore, stronger institutional coordination and enhanced restitution mechanisms are required to ensure that victims’ rights are fulfilled effectively and fairly.Keywords: restitution, crime victims, assault, restorative justice, legal protection.